The Problems Faced by Physicians While Preparing Death Certificates a Survey - Bilgin, Nursel Gamsız; Mert, Erhan (The Bulletin of Legal Medicine, 2003)
The data of the death reports and death certificate are used as data base for health statistics. The aim of this study was to determine the problems faced by physicians while completing death certificate, to recommend advices for the solution of this kind of problems and to stress the importance of this topic in education programmes either before or after graduation. Physicians of the Mersin University Medical Faculty Hospital were asked to complete the Questionnare with 14 open ended questions. Of 200 physicians who took questionnare, 87%(n=174) completed it. Of physicians who completed questionnare, 89.1% (n= 155) stated that they were completing death certificate for the permission of burial 70.7% of them thought that death certificate had to be completed by the physician who ascertained death and 71.84% of them stated that they had problems while completing these certificate. 51.1% of the physicians thought that the main underlying cause of death had to be written as the death cause, but %86.8 of the physicians stated that they did not use International Classification of Diseases (ICD). 93.1% of the physicians took lectures for the training of forensic medicine. In conclusion; it is very important to complete death certificate by writing underlying main cause of death according to the Intenational Classification of Diseases for maintaining accurate health statistical data and it is also important to put lessons regarding the procedures after death in the education programmes either before or after graduation Key words: Death certificate, forensic medicine education, health statistics